Effects of Growing-Season Prescribed Burning on Vigor of Sericea Lespedeza in the Kansas Flint Hills: II. Plant-Species Composition - J. A. Alexander; W. H. Fick; J. Lemmon; G. A. Gatson; G. W. Preedy; K C Olson (Kansas Agricultural Experiment Station Research Reports, 2017)
Fire has, for centuries, been a key force for sustainability of native ecosystems in the Kansas Flint Hills. Prior to the arrival of European settlers, prescribed and wild fires occurred at less than 3-year intervals in the tallgrass prairie region. As a result, native tallgrass plant communities adapted to fire at regular intervals and plant-species composition became stable on a geologic time scale. Currently, prescribed fire is used in the Kansas Flint Hills as a treatment for control of woody-stemmed invasive species such as eastern red cedar, honey locust, and roughleaf dogwood. These fires are generally applied in March and April and have become an integral part of the most common grazing management practice in the Kansas Flint Hills: annual spring burning in April followed by intensive grazing with yearling beef cattle for a relatively short period of time from late April to early August. Annual burning reportedly results in 0.2 to 0.3 lb of additional daily weight gain for yearling cattle when used in that way. In contrast, prescribed and wild fires during the presettlement era were not concentrated during any particular season of the year. Use of prescribed burning that is limited to a short interval during the spring has coincided with a steady increase of an invasive, non-woody, perennial legume known as sericea lespedeza (Lespedeza cuneata). Introduced into North America during the late 19th century, sericea lespedeza has proven highly adaptable to Flint Hills soils and climate. Prolific seed production appears to be the primary means of invasion. Seeds of sericea lespedeza are not wind-borne but are easily transported via the digestive tract of tannin-resistant herbivores and via machinery. Until recently, control of sericea lespedeza has relied heavily on costly, repeated application of herbicides, which has not checked the spread of the plant. We previously reported that prescribed burning during the months of August and September had strong suppressive effects on stand vigor and seed production of sericea lespedeza at a greatly reduced cost compared with herbicide. Questions remain, however, about the effects of growing-season prescribed burning on non-target plant species and soil cover. Therefore, the objective of this study was to evaluate the effects of growing-season prescribed fire on soil cover and populations of native grasses, forbs, and shrubs.
Keywords: sericea lespedeza; prescribed burning; growing season